Criminal Liability of Police Officers for Assault Resulting in Death: The Bripda Mesias Case in Tual City - Abdul Munim; Noenik Soekorini; Renda Aranggraeni (Jurnal Ilmiah Hukum dan Hak Asasi Manusia, 2026)
Purpose: This study analyzes the criminal liability of police officers for assault resulting in death through the 2026 case of Police Brigadier Mesias in Tual City. It examines applicable criminal law provisions, law enforcement mechanisms, and judicial processes, while proposing reforms to strengthen police accountability in Indonesia.Research Methodology: The study employed a normative-empirical legal approach using statutory, case, conceptual, and comparative analyses. Data were collected through interviews, observations, document reviews, and literature studies, then analyzed using juridical, content, and thematic techniques with triangulation to ensure validity.Results: The findings show that all elements of Article 351(3) of the Indonesian Criminal Code were fulfilled. Police officers do not enjoy criminal immunity, and the defense of acting in an official capacity was rejected because the use of force violated the principles of necessity and proportionality. The court imposed a five-year prison sentence, considering both aggravating and mitigating factors.Conclusions: Accountability is hindered by limited independence in internal investigations, corps solidarity, sentencing disparities, and weak witness protection. Public and civil society pressure played a significant role in ensuring accountability. Institutional reforms are needed to strengthen transparency and independent oversight.Limitations: The study focuses on a single case, limiting broader generalization. Access to internal police documents was restricted.Contributions: The study advances scholarship on police accountability, provides a framework for dual accountability, and offers practical insights for legal reform and policymaking.